ASSESSMENT OF COMPUTATIONAL THINKING: SEBUAH KAJIAN LITERATUR SISTEMATIS - Rahim, Fanny Rahmatina; Widodo, Ari; Riksa Yustiana, Yusi; Ha, Minsu (STKIP Pesisir Selatan, 2023)
The main objective of this study was to conduct a systematic literature review of the evaluation of computational thinking skills. The research method utilized was a comprehensive search of various databases through Google Scholar using the keyword